Functional and Structural Changes in the Membrane-Bound O-Acyltransferase Family Member 7 (MBOAT7) Protein: The Pathomechanism of a Novel MBOAT7 Variant in Patients With Intellectual Disability - Lee, Jiwon; Shamim, Amen; Park, Jongho; Jang, Ja-Hyun; Kim, Ji Hye; Kwon, Jeong-Yi; Kim, Jong-Won; Kim, Kyeong Kyu; Lee, Jeehun (Frontiers in Neurology, 2022)
The membrane-bound O-acyltransferase domain-containing 7 (MBOAT7) gene is associated with intellectual disability, early onset seizures, and autism spectrum disorders. This study aimed to determine the pathogenetic mechanism of the MBOAT7 missense variant via molecular modeling. Three patients from a consanguineous family were found to have a homozygous c.757G>A (p.Glu253Lys) variant of MBOAT7. The patients showed prominent dysfunction in gait, swallowing, vocalization, and fine motor function and had intellectual disabilities. Brain magnetic resonance imaging showed signal changes in the bilateral globus pallidi and cerebellar dentate nucleus, which differed with age. In the molecular model of human MBOAT7, Glu253 in the wild-type protein is located close to the backbone carbonyl oxygens in the loop near the helix, suggesting that the ionic interaction could contribute to the conformational stability of the funnel. Molecular modeling showed that Lys253 in the mutant protein was expected to alter the surface charge distribution, thereby potentially affecting substrate specificity. Changes in conformational stability and substrate specificity through varied ionic interactions are the suggested pathophysiological mechanisms of the MBOAT7 variant found in patients with intellectual disabilities.